Continuous flash sintering. Issue 4 (15th November 2017) - Sortino, Emanuele; Lebrun, Jean‐Marie; Sansone, Andrea; Raj, Rishi
Abstract: We develop an algorithm that relates the incubation time for flash initiation to the workpiece velocity as it is pulled through stationary electrodes in a continuous flash sintering experiment. Experiments with a whiteware green body that is sintered in this way are compared with the model. A processing map when the workpiece is drawn at a constant velocity is developed. The parameter space for the map is given by the speed and the current flowing through the workpiece. It distinguishes between the regimes for uniform and inhomogeneous sintering. All experiments were carried out at a furnace temperature of 900°C. The study shows the viability of continuous flash sintering of ceramics at speeds of up to 3 mm s −1 with electrodes that form a line contact with the workpiece. Remarkably, higher velocities and higher currents yield better sintering.